Modeling and prediction for gas production during coalbed methane drainage based on two indirect reservoir parameters. Issue 6 (November 2018) - Zou, Mingjun; Lv, Xiaochun; Huang, Zhiquan; Wei, Simin; Zhang, Miao; Sun, Changxin
Two indirect parameters influencing coalbed methane (CBM) drainage performances are proposed in this paper, which are effective desorption radius and difference between reservoir pressure and critical desorption pressure (DRPCDP). Variations of the two parameters during CBM drainage are investigated, which shows that they have a linear relationship. By using formula derivations, a theoretical model for gas production prediction is built. It suggests that the cumulative gas production is a product of square of effective desorption radius with DRPCDP, and there is also a cubic polynomial relationship between cumulative gas production and linear average DRPCDP. Furthermore, well PM01 located at southern Qinshui basin of China is selected as a case, and a commercial software is adopted to predict the gas production. Compared with the simulated and modeled cumulative gas productions, the simulated data match well with the modeled data, which indicates that the model has a good accuracy.